Analysis of Factors Influencing Life Cycle Costs of Transformers Based on TOPSIS Method - Long Zhan; Hui Chang; Xiaolu Zhu; Xin Zhao; Gang Wei; Ziyu Cai; Haibin Xie; Xinyue Zhao; Heng Chen (Energies)
The transformer is an essential piece of equipment in a power system, and its selection is directly related to the security, stability, and economics of the power system. This paper presents a comprehensive investigation into the life cycle costs (LCCs) of transformers. Our analysis of multiple samples delves into the composition and influencing factors in transformer life cycle costs. The findings reveal that the voltage level exerts a significant influence on cost, with higher voltage levels typically associated with greater costs. Moreover, the proportion of each cost component within the life cycle cost remains relatively stable. For this paper, we also conducted a weighted assessment of life cycle cost factors utilizing the TOPSIS method and determined that the voltage level and wiring method have the most substantial impact. In addition, the specific effects of the voltage level, wiring method, transformer type, and cooling method on LCCs are investigated using the control variable method. At the same time, the coupling influence of the wiring method, transformer type, and cooling method on transformer programs of different voltage levels is considered, which provides an essential reference for power grid enterprises in making engineering and construction investments.